The contribution of the smartphone use to reducing depressive symptoms of Chinese older adults: The mediating effect of social participation - Ji, Rong; Chen, Wei-chao; Ding, Meng-jun (Frontiers in Aging Neuroscience, 2023)
Depression is a common mental health disorder. While Internet use is associated with depression, limited data regarding the association of smartphone use with depression symptoms. We aimed to investigate the association between smartphone use and depressive symptoms of the elderly in China. Empirical study shows that smartphone use has a negative effect on depressive symptoms in the elderly. Endogenous and robustness tests verify the above result. The heterogeneity analysis shows that the elderly with the following characteristics have a greater association between smartphone use and depressive symptoms: aged 70 years and above, male, and from urban areas. Additionally, the mediating effect model shows political participation, voluntary participation, and active leisure participation play a mediating role in the relationship between smartphone use and lower levels of depression symptoms among the elderly. However, passive leisure participation plays a suppressing role between smartphone use and fewer depressive symptoms among the elderly.